2020
DOI: 10.3390/ijerph17155460
|View full text |Cite
|
Sign up to set email alerts
|

The Employability Process of Spanish Retired Elite Athletes: Gender and Sport Success Comparison

Abstract: The aims of the study were: (i) to describe the work integration after retirement in elite athletes, (ii) to compare the working integration of women and men, and Olympic and non-Olympic athletes, and (iii) to specify the factors that affect their employment status and current monthly income. A total of 476 former elite athletes were surveyed. Non-parametric statistics were applied to compare the differences between groups and a classification tree analysis was performed for the dependent variables. The former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…occupying a lower professional position than expected based on their educational level), was observed in only 5.8% of athletes (Conzelmann and Nagel, 2003). Similar findings were reported by López de Subijana et al (2020) who found a lower unemployment rate among former elite athletes in Spain (see also Barriopedro et al, 2018). However, there was no difference in the average monthly income between former athletes and the general population.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…occupying a lower professional position than expected based on their educational level), was observed in only 5.8% of athletes (Conzelmann and Nagel, 2003). Similar findings were reported by López de Subijana et al (2020) who found a lower unemployment rate among former elite athletes in Spain (see also Barriopedro et al, 2018). However, there was no difference in the average monthly income between former athletes and the general population.…”
Section: Introductionsupporting
confidence: 88%
“…In order to take the socio-economic status of an athlete's family of origin into account (cf. López de Subijana et al, 2020), school-leaving certificates and occupational prestige of the siblings, where present, were assessed. In addition, the parental socio-economic status was assessed by transforming coded job titles (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, it has been found that sports federations and other sports organizations should promote gender policies and create ad hoc programs to promote equality in all areas of sports [29,50]. In agreement with this, previous research studies have pointed out the importance of the social context and the need for stakeholder support to enable the holistic development of the female athlete [41,45], which allows not only their growth in sports, but also their educational progress with their inclusion in dual career programs [51,52], and the resulting employment success during and after their active careers [53,54]. These factors are essential for achieving the complete disappearance of the gender gap in sports [41,53].…”
Section: Plos Onementioning
confidence: 80%